Growth and distribution of soybean roots at different plant densities (Revista de Ciências Agroveterinárias, 2018)
The soybean plant has long been known to have a high phenotypic plasticity, altering shoot morphological traits in response to variations on plant density. However, plant density effects on soybean root growth and distribution in the soil profile are not elucidated. This paper aimed at evaluating the effects of three plant densities on soybean root growth at different soil layers and horizontal positions relative to the crop planting row. The study comprised two field experiments carried out during 2014/2015 growing season in Londrina, PR, Southern Brazil, one with the soybean cultivar BRS 359 RR, and other with the cultivar BMX Potência RR.  Both experiments were laid out in a randomized complete block design and split-split-plot arrangement, with three replications. In the main plots, three soybean seeding rates (150; 300; and 450 thousand seeds ha-1) were distributed; in the subplots, five soil layers (0-10; 10-20; 20-30; 30-40 and 40-50 cm depth); and, in the sub-subplots, three horizontal sampling positions (row; interrow on the left; and interrow on the right). Higher soybean plant densities led to thinner roots, with greater growth towards the crop interrows and deeper soil layers, but the cultivars can affect this behavior.
Keywords: Glycine max L.; root dry matter density; root surface area; root length density; root diameter